Analisis Perbandingan Nilai Perusahaan Sebelum dan Sesudah Penerapan Corporate Social Responsibility (CSR) (Studi Kasus pada Perusahaan Pertambangan yang Terdaftar di BEI) - Faulina, Melania (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This study compares firm value before and after the implementation of Corporate Social Responsibility in mining companies listed on the Indonesia Stock Exchange. The study employs a quantitative comparative approach using secondary data obtained from annual reports, sustainability reports, and financial statements. The sample was selected through purposive sampling and consisted of 14 mining companies. Firm value was measured using Tobin’s Q for the three-year period before and the three-year period after CSR implementation. Data were analyzed using descriptive statistics, normality testing, and a paired-samples t-test with SPSS version 29. The results show that the average Tobin’s Q increased from 1.1771 before CSR implementation to 1.5974 after implementation. The paired-samples t-test produced a significance value of 0.024, indicating a significant difference in firm value before and after CSR implementation. These findings suggest that CSR implementation is associated with an increase in the market valuation of mining companies.